Cotton plants as ideal models for teaching and research on inducible direct plant defenses - Mamin, Marine; Vallat, Armelle; Turlings, Ted C. J. (Frontiers in Ecology and Evolution, 2023)
Cotton (Gossypium hirsutum) stores defensive compounds in glands covering its leaves and other tissues. The density and the chemical filling of these glands increase systematically in developing leaves in response to herbivory on older leaves. Cotton seedlings are known to respond more strongly to actual caterpillar herbivory than to mere physical damage. It is not clear whether this amplified response is linked to insect-derived elicitors or difference in damage properties. To investigate this, we assessed the effect of repeated artificial damage without and with application of regurgitant from Spodoptera exigua caterpillars. Repeated mechanical damage led to a systemic increase of gland density, gland size, and content of defensive terpenes, with no detectable additional elicitation upon regurgitant treatment. Dual choice feeding assays further showed that defense induction triggered by just physical damage made newly developing leaves far less palatable to S. exigua larvae as compared to leaves from undamaged seedlings, whereas they did not distinguish between leaves from damaged plants treated with or without regurgitant. Our study confirms that the systemic induction of cotton glands is a nonspecific response to physical damage, although cotton is known to respond to caterpillar-associated elicitors for other defensive traits. Cotton glands induction can be readily visualized under modest magnification, making cotton, the method of repeated damage and the experiments described in this study highly suited as a model to teach chemical ecology and aspects of plant defense theory in practical classes.